Diagnostic Ability of Elevated 1- hour Glucose Challenge Test - A. TEMMING, Lorene (J Perinatol, 2016)
OBJECTIVE: To determine if a threshold of a 1-hour glucose challenge test (GCT) eliminates the need for a 3-hour glucose tolerance test (GTT). STUDY DESIGN: A retrospective cohort of patients undergoing GTT after GCT was ≥140 mg/dL. GDM was diagnosed using National Diabetes Data Group (NDDG) and Carpenter Coustan(CC) criteria. Sensitivity, specificity, and predictive values were calculated for 1-hour GCT values of 160 to 220 mg/dL. RESULT: Of 6218 patients, 988(15.9%) had an elevated GCT and 753(12.1%) underwent a GTT. 165(2.7%) were diagnosed with GDM using NDDG criteria, and 250(4.0%) by CC criteria. The positive predictive value of a 1-hour GCT≥200 mg/dL for GDM was 68.6% by NDDG and 80.0% for GDM by CC criteria. CONCLUSION: Although the predictive value of an elevated 1-hour ≥200 mg/dL for GDM was high, 1 in 3 to 1 in 5 women would be overdiagnosed with GDM if the 3-hour GTT were omitted.